Developments in the field of clinical allergy in 2015 through the eyes of Clinical and Experimental Allergy. Issue 11 (November 2016) - Roberts, G.; Boyle, R.; Bryce, P. J.; Crane, J.; Hogan, S. P.; Saglani, S.; Wickman, M.; Woodfolk, J. A.
Summary: In the second of two papers, we describe developments in the field of clinical allergy as documented by Clinical and Experimental Allergy in 2015. Epidemiology, clinical allergy, asthma and rhinitis are all covered. Abstract : This article is part 2 of the 'Year in Review' published in October: DOI:10.1111/cea.12823 .